Multiphase lattice Boltzmann methods : theory and application - Huang, Haibo (Engineering professor); Sukop, Michael C.; Lu, Xi-Yun. (Chichester, West Sussex, UK : Hoboken, New Jersey John Wiley and Sons, Inc., 2015)
Theory and Application of Multiphase Lattice Boltzmann Methods presents a comprehensive review of all popular multiphase Lattice Boltzmann Methods developed thus far and is aimed at researchers and practitioners within relevant Earth Science disciplines as well as Petroleum, Chemical, Mechanical and Geological Engineering. Clearly structured throughout, this book will be an invaluable reference on the current state of all popular multiphase Lattice Boltzmann Methods (LBMs). The advantages and disadvantages of each model are presented in an accessible manner to enable the reader to choose the.
4.3 Theoretical analysis (Chapman-Enskog expansion)4.3.1 Discussion of above formulae; 4.4 Layered two-phase flow in a 2D channel; 4.4.1 Cases of two fluids with identical densities; 4.4.2 Cases of two fluids with different densities; 4.5 Interfacial tension and isotropy of the RK model; 4.5.1 Interfacial tension; 4.5.2 Isotropy; 4.6 Drainage and capillary filling; 4.7 MRT RK model; 4.8 Contact angle; 4.8.1 Spurious currents; 4.9 Tests of inlet/outlet boundary conditions; 4.10 Immiscible displacements in porous media; 4.11 Appendix A; 4.12 Appendix B.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Lattice Boltzmann methods; Multiphase flow; Fluid dynamics; Fluid dynamics -- Mathematical models; Fluid dynamics; Fluid dynamics -- Mathematical models; Lattice Boltzmann methods; Multiphase flow; SCIENCE / Energy; SCIENCE / Mechanics / General; SCIENCE / Physics / General; Fluid dynamics -- Mathematical models; Fluid dynamics; Lattice Boltzmann methods; Multiphase flow; Electronic books